The Impact of Delivery Type on Ventricular Performances of Healthy Neonates - Erman Cilsal (Gynecology Obstetrics & Reproductive Medicine)
Objective: The present study aims to evaluate how the mode of delivery affects the alterations in myocardial functions of healthy newborns within the first month of life.